Housing markets, expectation formation and interest rates - Carolin Martin; Noemi Schmitt; Frank Westerhoff (Bamberg University, Bamberg Economic Research Group (BERG), 2019)
Based on a behavioral stock-flow housing market model in which the expectation formation behavior of boundedly rational and heterogeneous investors may generate endogenous boom-bust cycles, we explore whether central banks can stabilize housing markets via the interest rate. Using a mix of analytical and numerical tools, we find that the ability of central banks to tame housing markets by increasing the base (target) interest rate, thereby softening the demand pressure on house prices, is rather limited. However, central banks can greatly improve the stability of housing markets by following an interest rate rule that adjusts the interest rate with respect to mispricing in the housing market.
Keywords: D91; E58; R31; 330; housing markets; heterogeneous expectations; variance beliefs; endogenous boom-bust cycles; interest rates; nonlinear dynamics